Right Circulant Matrices with Jacobsthal Sequence - Bueno, Aldous Cesar Fernando (International Journal of Advanced Mathematical Sciences, 2013)
In this paper, the eigenvalues, Euclidean norm and inverse of right circulant matrices with Jacobsthal sequence were obtained.